Si Blorok: Mother Figure as Performer of Islamic Education Values in Dongenge Pitik karo Bebek - Arum Rindu Sekar Kasih; Ummi Nurjamil Baiti Lapiana; Ika Oktaviana (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
A fairy tale is a media parents use to instill good values ​​in children. In fairy tales, children can learn values embedded to strengthen their value education. One of the figures who often has a vital role in conveying values and becomes a role model is a mother figure. The mother figure in children’s stories or fairy tales can inspire parents in the family or teachers at school by providing an example of good behavior to the children. This study focused on Islamic education values in the character of Si Blorok, portrayed as a mother figure. This study used a qualitative descriptive approach by analyzing the character of Si Blorok. The data source was a fairy tale entitled